2009
DOI: 10.1890/08-2224.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dynamics of nesting behavior: Lizards shift microhabitats to construct nests with beneficial thermal properties

Abstract: Because temperature affects the growth, development, and survival of embryos, oviparous mothers should discriminate carefully among available nesting sites. We combined a radiotelemetric study of animal movements with a spatial mapping of environmental temperatures to test predictions about the nesting behavior of the eastern fence lizard (Sceloporus undulatus). Females made large excursions from their typical home ranges to construct nests in exposed substrates. These excursions appeared to be related solely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 50 publications
2
104
1
Order By: Relevance
“…Although several studies demonstrated the availability of environmental temperatures for T p,o in terrestrial habitats (Kingsolver 1979;Shine and Harlow 1996;Warner and Shine 2008;Angilletta et al 2009), our results show that even in aquatic, i.e. more thermally harsher, environments vertical thermal stratification enables females to chose between thermally more or less suitable sites for oviposition.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Although several studies demonstrated the availability of environmental temperatures for T p,o in terrestrial habitats (Kingsolver 1979;Shine and Harlow 1996;Warner and Shine 2008;Angilletta et al 2009), our results show that even in aquatic, i.e. more thermally harsher, environments vertical thermal stratification enables females to chose between thermally more or less suitable sites for oviposition.…”
Section: Discussioncontrasting
confidence: 70%
“…This suggests the anticipatory maternal effect of oviposition temperature preferences, referred to as the maternal manipulation hypothesis (Webb et al 2006). However, the evidence for the maternal preference-offspring performance matching, mostly stems from laboratory experiments with no or limited information about thermal conditions in natural populations (but see Angilletta et al 2009). The adaptive significance of this transgenerational coadaptation depends, among others, on how closely preferred oviposition temperatures approach local phenotypic optimum (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…On each day of the year, we allocated a nest to microhabitats with each combination of shade (0, 25, 50, 75 or 100%) and depth (3, 6, 9 or 12 cm). These combinations captured the range of microhabitats for natural nests [24]. For each nest, we calculated: (i) minimal and maximal temperatures, (ii) the mean survival rate of embryos, (iii) the mean incubation period, and (iv) the number of days between hatching and winter dormancy (i.e.…”
Section: (C) Modelling the Performance Of Embryosmentioning
confidence: 99%
“…Thermal stress can occur daily during a brief period in the afternoon when soil temperatures peak. Although embryos cannot survive prolonged exposure to such extremes [25,26], they grow and develop rapidly during brief daily exposures [14,24]. Still, even a brief exposure to a temperature of sufficient magnitude causes death by cardiac arrest [27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kearney and Porter (2004) expressed thermal GIS layers as the minimum number of degree-days required by a clutch of Heteronotia binoei eggs to hatch, and Lovvorn et al (2009) expressed viable habitat as pixels where energy intake was greater than energy cost. Angilletta et al (2009) compared predicted and measured temperatures at nest sites via a spatially-explicit model of soil temperatures. Application of prey and predator spatial distribution is not as easily achieved, but future research may benefit from comparing suitability models for those taxa as input features for a study species' own ecological niche model …”
Section: Model Validationmentioning
confidence: 99%